Studi Kenyamanan Termal Siswa Sekolah Dasar Negeri (Studi Kasus: Sekolah Dasar Negeri 06 Sukabumi Selatan, Jakarta Selatan) - Randy Dwiyan Delyuzir; Bima Murdilangga; Helvin Husni Assidik; Hani Susmita (Institut Teknologi Sains Bandung, 2023)
Thermal comfort studies have been carried out at Public Elementary School 06 Sukabumi Selatan, Jakarta, Indonesia. The schools that were observed were public schools that relied only on natural ventilation. Climatic parameters, namely air temperature and radiation temperature, relative humidity, and air speed were recorded together with the choice of seven scale subject comfort. The number of students in the state school was 82 people, consisting of 39 boys and 43 girls who were involved in this study. The study subjects were between 8 and 13 years old in public schools. The comfortable temperature of students at Public School 06 Sukabumi Selatan is 27.82°CTa higher than the current Indonesian comfort standard. This research examines the entire study and draws some conclusions from it